Answer:
y=3
Step-by-step explanation:
Let's solve your equation step-by-step.
5y−3y+1=7
Step 1: Simplify both sides of the equation.
5y−3y+1=7
5y+−3y+1=7
(5y+−3y)+(1)=7(Combine Like Terms)
2y+1=7
2y+1=7
Step 2: Subtract 1 from both sides.
2y+1−1=7−1
2y=6
Step 3: Divide both sides by 2.
2y
/2
=
6
/2
y=3
<h3>
Answer:</h3>
4. -3
5. 3
<h3>
Step-by-step explanation:</h3>
4. For x > -2, the value of a is the slope of the line. The line goes down 3 units for each 1 to the right, so the slope is -3/1 = -3. Then a = -3.
___
5. The ordered pair (h, k) is typically used to name the point to which a function is translated. The vertex of the function f(x) = |x| is (0, 0). When it is translated to (h, k), the function becomes ...
... q(x) = |x -h| +k
If the new vertex is (3, 0), then h = 3 and k = 0. This is consistent with the equation shown. (k = 0 means q(x) = |x -h|.)
Answer:
I hope this helps
Step-by-step explanation:
-3 1/8